Bilateral striatal necrosis caused by ADAR mutations in two siblings with dystonia and freckles-like skin changes that should be differentiated from Leigh syndrome - Piekutowska-Abramczuk, Dorota; Mierzewska, Hanna; Bekiesińska-Figatowska, Monika; Ciara, Elżbieta; Trubicka, Joanna; Pronicki, Maciej; Rokicki, Dariusz; Rydzanicz, Małgorzata; Płoski, Rafał; Pronicka, Ewa (Folia Neuropathologica, 2016)
Pathogenic molecular variants in the ADAR gene are a known cause of rare diseases, autosomal recessive Aicardi- Goutières syndrome type 6, severe infantile encephalopathy with intracranial calcifications and dominant dyschromatosis symmetrica hereditaria, demonstrated mainly in Asian adults. Recently, they have been also found in patients with nonsyndromic bilateral striatal necrosis accompanied by skin changes of the freckles-like type. Here, we present Polish siblings with acute onset and slowly progressive extrapyramidal syndrome with preserved intellectual abilities and basal ganglia changes found in MRI. A Leigh syndrome was considered for a long time as the most frequent cause of such lesions in children. Finally, two molecular variants in non-mitochondria-related ADAR gene c.3202+1G>A (p.?) and c.577C>G (p.Pro193Ala) were revealed by whole exome sequencing. We suggest that bilateral striatal necrosis should be always differentiated from LS to prevent the diagnosis delay. The striatal involvement accompanied by the presence of freckles-like skin changes should direct differential diagnosis to the ADAR gene mutations screening.